Veterinary Guidelines for Electrochemotherapy of Superficial Tumors - Tellado, Matías; Mir, Lluis M.; Maglietti, Felipe (Frontiers in Veterinary Science, 2022)
Electrochemotherapy consists in the application of electric pulses to increase chemotherapeutic drug intake (bleomycin, cisplatin, or calcium) into the tumor cells. It has become a very valuable treatment option in veterinary oncology. It is an effective and safe treatment modality, which is not only beneficial as a palliative treatment, but also for a curative approach. Performing the treatment adequately will ensure the best results possible, in the minimum number of sessions, and reduce complications. Usually, only one session is enough to achieve excellent results, but the treatment can be repeated. Several sessions can be necessary in the case of incompletely treated lesions or very extended lesions, as well as in the case of the occurrence of new lesions. ECT is effective for superficial or oral tumors of any histology that are accessible to the electrodes. Intravenous bleomycin is the preferred drug and route of administration for almost all cases, leaving other ways of administration and drugs for selected cases. The standard operating procedures here reported are based on more than 10 years of experience in treating veterinary cancer patients, and on the preparation of theoretical and practical courses along this time. These SOP are destined for veterinarians who want to develop their understanding of the basis of ECT and wish to perform it adequately and effectively. In this paper, we also discuss common problems, how to solve them, and we include practical tips to improve the treatment results based on common questions that arose during the courses.